Can a combination of poly(ethylene glycol) and dense phase carbon dioxide improve processing of polylactide? A high pressure rheology investigation - Pepper, Katie; Masson, Timothé; De Focatiis, Davide S.A.; Howdle, Steven M. (Elsevier, 2017)
High temperature melts or use of organic solvents are not practicable approaches for encapsulating protein based or thermally labile drugs into degradable polymers. Here, we demonstrate that poly(ethylene glycol) (PEG) in combination with supercritical carbon dioxide (scCO2) can dramatically reduce the viscosity of polymer melts allowing enhanced uptake of CO2 into poly(D,L-lactide) (PLA). Both PEG and CO2 are approved excipients in drug delivery and it is well documented that individually both are effective plasticisers. Using high pressure rheology techniques (scCO₂ at 14 MPa) we demonstrate a synergistic impact leading to significantly lower processing temperatures with PEG employed as both a blended additive and as a component of a block copolymer.